2018
DOI: 10.1111/odi.12981
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic and health status as a predictor of apical periodontitis in adult patients in Croatia

Abstract: Objective A few studies focused on determinants of apical periodontitis other than technical or biological factors. This research aimed to investigate to what extent socio‐economic and health status can predict apical periodontitis in adult patients. Subjects and Methods The cross‐sectional study included 599 adult patients. Medical history, health habits and socio‐economic status of each participant were recorded using a self‐administered structured questionnaire. For caries detection, the World Health Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
2
5
1
Order By: Relevance
“…The older the patient, the greater the likelihood of being affected by AP in a tooth. This is also consistent with earlier observations (Alrahabi & Younes, 2016;Kielbassa et al, 2017;Persic Bukmir et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…The older the patient, the greater the likelihood of being affected by AP in a tooth. This is also consistent with earlier observations (Alrahabi & Younes, 2016;Kielbassa et al, 2017;Persic Bukmir et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…The scientific literature contains conflicting evidence relating smoking habits and AP or RCT (Aminoshariae et al, 2020; Duncan & Pitt Ford, 2006; Segura‐Egea et al, 2015; Walter, Rodriguez, et al, 2012). There are many studies that have found a significant association between smoking and the prevalence of periapical lesions of endodontic origin (Aleksejuniene et al, 2000; Doyle et al, 2007; Kirkevang et al, 2007, 2017; Kirkevang & Wenzel, 2003; Krall et al, 2006; López‐López et al, 2012; Oginni et al, 2015; Persic Bukmir et al, 2019; Segura‐Egea et al, 2008, 2011). A systematic review concluded that smokers have a prevalence of AP and RCT that is greater than 2.5 times higher than nonsmokers (Pinto et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…RCT has been shown to be almost two times more prevalent in smokers, with a dose-response relationship (Krall et al, 2006). However, other studies found no association between smoking and the prevalence of AP (Bergström et al, 2004;Frisk & Hakeberg, 2006;Rodriguez et al, 2013) or the frequency of RCT (Bergström et al, 2004;Persic Bukmir et al, 2019).…”
Section: Smoking Habitsmentioning
confidence: 99%
“…Consequently, periapical bone destruction could be greater in smokers, altering periapical repair after root canal treatment, increasing the number and/or size of periapical lesions [20]. Table 4 summarizes the characteristics and main findings of clinical studies that assessed the association between endodontic parameters and smoking habits [128][129][130][131][132][133][134][135][136][137][138][139][140].…”
Section: Smoking Habitsmentioning
confidence: 99%
“…The scientific evidence relating smoking habits and AP or root canal treatment is conflicting [20,141,142]. Although some studies have found no association between smoking and the prevalence of AP [128,[138][139][140], several other studies have reported significant association between smoking and the prevalence of AP [128][129][130][131][132][133][134][135][136][137]. Two retrospective studies have found that RCT in smokers had fewer successes and more failures than in non-smoker patients [140,143].…”
Section: Confirmedmentioning
confidence: 99%